Root-Specific Expression of OsNAC10 Improves Drought Tolerance and Grain Yield in Rice under Field Drought Conditions(1)([W])([OA]) - Jeong, Jin Seo (American Society of Plant Biologists, 2010)
Drought poses a serious threat to the sustainability of rice (Oryza sativa) yields in rain-fed agriculture. Here, we report the results of a functional genomics approach that identified a rice NAC (an acronym for NAM [No Apical Meristem], ATAF1-2, and CUC2 [Cup-Shaped Cotyledon]) domain gene, OsNAC10, which improved performance of transgenic rice plants under field drought conditions. Of the 140 OsNAC genes predicted in rice, 18 were identified to be induced by stress conditions. Phylogenic analysis of the 18 OsNAC genes revealed the presence of three subgroups with distinct signature motifs. A group of OsNAC genes were prescreened for enhanced stress tolerance when overexpressed in rice. OsNAC10, one of the effective members selected from prescreening, is expressed predominantly in roots and panicles and induced by drought, high salinity, and abscisic acid. Overexpression of OsNAC10 in rice under the control of the constitutive promoter GOS2 and the root-specific promoter RCc3 increased the plant tolerance to drought, high salinity, and low temperature at the vegetative stage. More importantly, the RCc3:OsNAC10 plants showed significantly enhanced drought tolerance at the reproductive stage, increasing grain yield by 25% to 42% and by 5% to 14% over controls in the field under drought and normal conditions, respectively. Grain yield of GOS2:OsNAC10 plants in the field, in contrast, remained similar to that of controls under both normal and drought conditions. These differences in performance under field drought conditions reflect the differences in expression of OsNAC10-dependent target genes in roots as well as in leaves of the two transgenic plants, as revealed by microarray analyses. Root diameter of the RCc3:OsNAC10 plants was thicker by 1.25-fold than that of the GOS2:OsNAC10 and nontransgenic plants due to the enlarged stele, cortex, and epidermis. Overall, our results demonstrated that root-specific overexpression of OsNAC10 enlarges roots, enhancing drought tolerance of transgenic plants, which increases grain yield significantly under field drought conditions.